Analisis Naratif Tzvetan Todorov pada Video Klip Lagu “Ayah” Karya Ebiet G. Ade dan Iwan Fals - Hans Hermang Mintana (Jurnal Ilmu Komunikasi AKRAB, 2026)
Music videos, as audiovisual communication media, serve not only as a means of promoting musicbut also as a medium for conveying messages through visual narratives that represent social andcultural values. One of the music videos that explores the theme of family relationships is Titip RinduBuat Ayah by Ebiet G. Ade and Iwan Fals, which portrays a father as a hardworking figure, aprotector, and a source of unconditional love within the family. This study aims to analyze thenarrative structure constructed in the music video using Tzvetan Todorov's narrative analysis theory.The research employs a qualitative approach with a descriptive-interpretative method. Data werecollected through repeated observations of the music video, scene documentation, and a literaturereview related to narrative theory and visual communication. The analysis was conducted based onTodorov's five stages of narrative structure: equilibrium, disruption, recognition, attempt to repair,and new equilibrium. The findings reveal that the music video constructs a linear narrative beginningwith the harmonious relationship between a father and his child, followed by conflicts arising fromdifferences in life perspectives and the father's aging process, the child's realization of the father'ssacrifices, efforts to reconcile with the loss by honoring the values inherited from the father, andultimately the establishment of a new equilibrium characterized by acceptance and emotionalmaturity. This narrative structure demonstrates that the music video not only visualizes the meaningof the song's lyrics but also constructs a representation of sacrifice, affection, responsibility, and thesignificant role of a father within the family. The study concludes that Tzvetan Todorov's narrativetheory is an effective framework for revealing the construction of narrative and meaning inaudiovisual media, particularly in music videos